Neuroprotective and Anti-inflammatory Effects of Pioglitazone on Traumatic Brain Injury - Zamanian, Mohammad Yassin; Taheri, Niloofar; Opulencia, Maria Jade Catalan; Bokov, Dmitry Olegovich; Abdullaev, Sharif Y.; Gholamrezapour, Mohammadreza; Heidari, Mahsa; Bazmandegan, Gholamreza (Mediators of Inflammation, 2022)
Traumatic brain injury (TBI) is still a major cause of concern for public health, and out of all the trauma-related injuries, it makes the highest contribution to death and disability worldwide. Patients of TBI continue to suffer from brain injury through an intricate flow of primary and secondary injury events. However, when treatment is provided in a timely manner, there is a significant window of opportunity to avoid a few of the serious effects. Pioglitazone (PG), which has a neuroprotective impact and can decrease inflammation after TBI, activates peroxisome proliferator-activated receptor-gamma (PPARγ). The objective of the study is to examine the existing literature to assess the neuroprotective and anti-inflammatory impact of PG in TBI. It also discusses the part played by microglia and cytokines in TBI. According to the findings of this study, PG has the ability to enhance neurobehavior, decrease brain edema and neuronal injury following TBI. To achieve the protective impact of PG the following was required: (1) stimulating PPARγ; (2) decreasing oxidative stress; (3) decreasing nuclear factor kappa B (NF-κB), interleukin 6 (IL-6), interleukin-1β (IL-1β), cyclooxygenase-2 (COX-2), and C-C motif chemokine ligand 20 (CCL20) expression; (4) limiting the increase in the number of activated microglia; and (5) reducing mitochondrial dysfunction. The findings indicate that when PIG is used clinically, it may serve as a neuroprotective anti-inflammatory approach in TBI.